The delicate distress - Griffin, Elizabeth, active 1799 (Eighteenth-century novels by women., 2015)
Actress, playwright, and novelist, Elizabeth Griffith (1727-1793) won fame in England with the publication in 1757 of the first two volumes of Letters Between Henry and Frances, letters from her own courtship with Richard Griffith whom she secretly married in 1751. Her first novel, The Delicate Distress (1769), focuses on the problems women encounter after marriage -- the issue of financial independence for wives, the consequences of interfaith relationships, and the promiscuity of their husbands. Against a backdrop of rural England and Paris of the ancien regime, Griffith reimagines the epi.